Unusual tandem ring closing metathesis–Claisen rearrangement enroute to spiro annulation of O-allyl biscoumarins. Issue 17 (22nd April 2015) - Yerrabelly, Jayaprakash Rao; Chakravarthula, Venu; Yerrabelly, Hemasri; Chitneni, Prasad Rao; Batchu, Venkateshwar Rao; Nanubolu, Jagadeesh Babu; Krishnan, Ravi Kumar
Graphical abstract: Abstract: A simple and efficient synthesis of new spiro heterocyclic skeleton, 3′-vinyl-2′, 3′-dihydrospiro[chroman-3, 4′-oxepino[3, 2- c ]chromene]-2, 4, 6′(5′ H )-triones by an unusual one pot tandem RCM–Claisen rearrangement of O -allyl biscoumarins is described. A new example of a coumarin derivative containing seven membered cyclic ether.